Production of functionalized liquid natural rubber from low grade natural rubber as a precursor for semi-rigid polyurethane / Radin Siti Fazlina Nazrah Hirzin - Radin Siti Fazlina Nazrah, Hirzin (2018)
Functionalized liquid natural rubber (FLNR) derived from low grade natural rubber (NR) was synthesized by in situ redox method using hydrogen peroxide (H2O2) in the presence of sodium nitrite (NaNO2). The formation of hydroxyl (OH) as a main functional group was confirmed by Fourier Transform Infrared (FTIR) spectroscopy with a peak at 3425 cm−1. The Nuclear Magnetic Resonance (NMR) spectroscopy showed the presence of central and end OH groups in the FLNR. Response surface methodology (RSM) optimization was used to investigate the effect of varying feed parameters towards response of molecular weights and OH values. The response surface contours were constructed for modeling the relationship between processing factors and response output. The developed models showed that NaNO2 was the main factor followed by H2O2 that influence the FLNR properties. Multi response optimization was done using Derringer’s desirability function. The optimum conditions for minimizing average number molecular weight (Mn) and molecular weight distribution (MWD) while maximizing OH value were determined to be at low ratios of NaNO2/H2O2 and high ratios of H2O2/isoprene unit. The predicted optimum response for Mn was around and less than 30,000 g/mol, polydispersity index (PDI) between 1.48 and 1.61 and OH value between 194 and 229 mg KOH/g. The optimization confirmation was done, and the minor error of percentage calculated from the predicted and observed responses was obtained. Gel Permeation Chromatography (GPC) was used to investigate of the reduction of molecular weight performance and OH autotitrator used to measure the OH values of FLNR. The selected optimum values of FLNR responses were used to produce a semi-rigid polyurethane (PU) precursor. The preparation of FLNR based semi-rigid PU was carried out by one-shot and two-shot methods. The urethane linkage formation was confirmed by FTIR with a peak at 3317 cm-1 due to -NH- and disappearance peak of the NCO at 2295 cm-1. A rubber polyol chain length as soft segment has shown to have a major implication in the polymer products due to the high soft segment content compared to hard segment content in the semi-rigid PU formulation. The semi-rigid character of the PU with low polyol chain length and high soft phase domain favoured solubility in non-polar solvent (toluene and chloroform) and low polar solvent (THF). As for high polyol chain, it was insoluble in any solvent thus its high stability. The differences in glass transition temperatures (Tg) obtained indicated stronger interaction between hard and soft segment by both of one-shot and two-shot method. The thermal stability behaviour as determined by thermogravimetry analyzer (TGA) showed that the two-shot method had improved the semi-rigid PU performance either at low or high value of polyol chain length. Studies on the chemical stability, hydrolytic stability and soil test degradation behaviour were shown to be influenced by the high soft segment contents in semi-rigid PU composition.